Z več znanja o motnjah razpoloženja do izhodov iz labirintov Izkušnje in razmisleki - Šprah, Lilijana (ZRC SAZU, Založba ZRC, 2019)
Mood disorders are becoming one of the major public health problems and care for good mental health is substantially affecting almost all dimensions of our lives. However, the lay and professional public have the most contrasting attitudes and beliefs about mental disorders compared to other chronic non-communicable diseases. Persisting stereotypes and myths about mental disorders as a rule hinder professional help-seeking, interest and belief in their effective treatment. This problematic is discussed in the multi-authored monograph ('More Knowledge about Mood Disorders for Escaping the Labyrinth: Experiences and Reflections'). In the 21 scientific and professional essays, the authors of various academic backgrounds reflect upon mental health issues, focusing on contemporary mood disorders. Moreover, the first results of the newly introduced and innovative mental health promotion programme in Slovenia - With Raised Mental Health Literacy to Better Managing Mood Disorders (acronym OMRA) - are presented, as well. The monograph is good food for thought for the lay and professional public.